Prevalence and Molecular Epidemiology of Extended-Spectrum-β-Lactamase (ESBL)-Producing Escherichia coli from Multiple Sectors of Poultry Industry in Korea - Hyunsoo Kim; Young Ah Kim; Young Hee Seo; Hyukmin Lee; Kyungwon Lee (MDPI AG, 2021)
The aim of this study was to investigate the molecular epidemiology of extended-spectrum-β-lactamase producing Escherichia coli (ESBL-EC) from poultry, the poultry farm environment, and workers in Korea. A total of 1376 non-duplicate samples were collected from 21 poultry farms, 20 retail stores, 6 slaughterhouses, and 111 workers in a nationwide study in Korea from January 2019 to August 2019. The overall positive rate of ESBL-EC was 6.8%, with variable positive rates according to sources (0.9% of worker, 5.2% of poultry, 10.0% of chicken meat, and 14.3% of environment). Common ESBL types were CTX-M-55 and CTX-M-14 in a total of 93 ESBL-EC isolates. Whole genome sequencing revealed that 84 ESBL-EC isolates had an outstanding accumulation of numerous antimicrobial resistance (AMR) genes associated with resistance to various classes of antimicrobials for human use and well-known antimicrobial gene (ARG)-carrying plasmids. Core gene multi locus sequence typing, using 2390 core genes, indicated no dominant clone or common type in each province. In conclusion, the isolation rates of ESBL-EC were not negligible in the poultry industry-related samples, sharing common ESBL types of human ESBL-EC isolates in Korea.